1983
DOI: 10.1295/polymj.15.835
|View full text |Cite
|
Sign up to set email alerts
|

The Second Virial Coefficient of Monodisperse Polystyrene in Cyclohexane below the Theta Point

Abstract: ABSTRACT:A light scattering study was made on monodisperse polystyrene + cyclohexane solutions in the range of molecular weight from 10000 to 500000 and that of temperature from 34.5°C (8) down to a value about I oc above the cloud point. The second virial coefficient A2 was found to depend essentially on temperature only, at least in the range of molecular weight examined. This result is not in conformity with any current two-parameter theories for A2 of polymer solutions.KEY As will be noted later, Wolf and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
18
1
Order By: Relevance
“…Here Xo is the concentration independent coefficient and Xo c is the critical Xo· Xo c is related to Tc, 1/1 0 , and 0 through the relation (22) Here v is the specific volume of polymer and note that 1/1 0 estimated by eq 22 corresponds to the finite molecular weight. 0 is determined as the temperature at which A 2 becomes zero.…”
Section: (B) Stockmayer Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here Xo is the concentration independent coefficient and Xo c is the critical Xo· Xo c is related to Tc, 1/1 0 , and 0 through the relation (22) Here v is the specific volume of polymer and note that 1/1 0 estimated by eq 22 corresponds to the finite molecular weight. 0 is determined as the temperature at which A 2 becomes zero.…”
Section: (B) Stockmayer Methodsmentioning
confidence: 99%
“…Ko values thus determined by Miyaki and Fujita scatter fairly largely, probably due to experimental difficulty of LS measurements of solutions of polymers with M w 10 7 • Ko= 0.22 at 308 K was obtained for M w = oo from line c in the figure, constructed by the least-squares method. Tong et al 22 determined A 2 of five monodisperse PS samples in the temperature range from 307.7 K to about 1 K above the cloud point and they found A 2 for monodisperse PS in CH below 0 to be independent of M, within the ranges of T and M studied. Since unfortunately the A 2 values were not described in their paper, we estimated (oA 2 /oT) 9 from the initial slope of the plot of -A 2 vs. T-1 (Figure 4 of ref 22 10 MiyakiFujita, 20 • 21 and Tong et al 22 The Ko value at infinite molecular weight for each study is shown in the table.…”
mentioning
confidence: 95%
“…On the other hand, ð@Å=@cÞ=RT for the fraction F1-2 with M w ¼ 10500 takes a minimum around " c c % 0:1 g/cm 3 at 15 C. Similar concentration dependencies of ð@Å=@cÞ=RT for cyclohexane solutions of polystyrene with M w % 10 4 near the temperature have already been reported previously. 14,15 From data points at low " c c, we have determined M w and A 2 for each fraction, using eq 5. The results are listed in Table I.…”
Section: Figure 1 Shows Double Logarithmic Plots Ofmentioning
confidence: 99%
“…Therefore, we can more critically test the perturbation theory by comparing it with the poor solvent system. So far, the osmotic compressibility of cyclohexane solutions of polystyrene was investigated over wide ranges of the concentration by several workers [11][12][13][14][15] However, most of them used rather high molecular weight polystyrene samples, and may not be suitable for the purpose of the present study. On the other hand, the second virial coefficient A 2 of oligo-and polystyrenes in cyclohexane over a wide molecular weight range was measured by Yamakawa et al 16,17 We have utilized their A 2 data to determine the interaction parameters d and " of polystyrene in cyclohexane, as explained below.…”
mentioning
confidence: 99%
“…The least squares parameters for the correlation lines are reported in Table III . The least squares parameters of the correlation lines are reported in Table III. CORRELATION OF OSMOTIC VIRIAL COEFFICIENTS WITH SOLVENT QUALITY by the observations of Tong et al 29 and Perzynski et al 30 for PS/CH and Takano et al 52 for polyisoprene/dioxane solutions. That work showed that the A 2 decays smoothly with T in the poor solvent region (T Ͻ ).…”
Section: Second Virial Coefficientsmentioning
confidence: 94%